(3CLhHI eSGFd Cgd CUagGfs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3ajbhd GdYHO GdeScjf(B: (3CMeO Hf Rjf GdOjf GdCMSGFj(B... (3Efg bO CJJ Edj HYV GdeSGFd ef HdO GdEeGQI hGdEjeGf(B...s
(3BNQgG (B:s
(3agPg CQHYjf hgj eQGJH GdhLhO(B... (3hEf cGf aj GdTgGOI agh OhQ hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds